2021
DOI: 10.1021/acs.jmedchem.1c01118
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Series of RIPK2 PROTACs

Abstract: Receptor-interacting serine/threonine protein kinase 2 (RIPK2) is an important kinase of the innate immune system. Herein, we describe the optimization of a series of RIPK2 PROTACs which recruit members of the inhibitor of apoptosis (IAP) family of E3 ligases. Our PROTAC optimization strategy focused on reducing the lipophilicity of the early lead which resulted in the identification of analogues with improved solubility and increased human and rat microsomal stability. We identified a range of IAP binders tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…The effectiveness of SNIPERs as degraders improved as IAP ligands with higher affinity towards IAPs were incorporated into bifunctional molecules. 71,233,[237][238][239][240][241][242][243][244][245] The first more evident leap in the degradation potency of SNIPERs was achieved by utilising LCL161 (IAP ligand C) as the recruiting ligand. 7,233 In this review, however, we focus on IAP ligands D, E, I, and J, because of synthetic simplicity or availability of reliable synthetic procedures, on target potency, and beneficial physicochemical properties.…”
Section: Important Iap Ligands Used For Tpd Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effectiveness of SNIPERs as degraders improved as IAP ligands with higher affinity towards IAPs were incorporated into bifunctional molecules. 71,233,[237][238][239][240][241][242][243][244][245] The first more evident leap in the degradation potency of SNIPERs was achieved by utilising LCL161 (IAP ligand C) as the recruiting ligand. 7,233 In this review, however, we focus on IAP ligands D, E, I, and J, because of synthetic simplicity or availability of reliable synthetic procedures, on target potency, and beneficial physicochemical properties.…”
Section: Important Iap Ligands Used For Tpd Applicationsmentioning
confidence: 99%
“…In addition, the exemplified PROTACs in the following sections were also extensively evaluated both in vitro and in vivo. E, I, and J, is given here: bestatin (IAP ligand A), 232,[234][235][236] MV1 (IAP ligand B), 238,239,244 LCL161 (IAP ligand C), 239,240,[243][244][245] IAP ligand F, 71,237 IAP ligand G, 241 IAP ligand H. 242 ligand (IAP ligand D, Fig. 15) is a beneficial IAP recruiter for targeted protein depletion.…”
Section: Important Iap Ligands Used For Tpd Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, due to the discovery that immunomodulatory drugs (IMiDs), including thalidomide, lenalidomide and pomalidomide, could act as ligands for the E3 ligase CRBN, a large number of CRBN-based PROTACs were successfully developed to degrade BRD4 [ 13 ], CDK9 [ 14 ], Sirt2 [ 15 ], KRAS G12C [ 16 ], AKT [ 17 ], HDAC6 [ 18 ] and CDK6 [ 19 ]. Similarly, VHL-based PROTACs have successfully degraded ERRα [ 20 ], RIPK2 [ 21 ], HaloTag7 fusion proteins [ 22 ], BRD4 [ 23 ], Smad3 [ 24 ] and RTK [ 25 ], and RNF114-based PROTACs have degraded BRD4 [ 26 ] and BCR-ABL [ 26 , 27 ]; IAP-based PROTACs have degraded RIPK2 [ 28 ], CDK4/6 [ 29 ], Bcl-XL [ 29 ], etc. In more recent years, the explosive growth of PROTACs has indicated that PROTAC is becoming the most popular drug development technology.…”
Section: Development History Of Protacmentioning
confidence: 99%